Kinoteatrcyrk. Bruno Schulz i medialna episteme awangardy - Tomczok, Paweł (Przestrzenie Teorii, 2024)
The aim of the article is to discuss the media topics in the prose of Bruno Schulz in the context of the media reflection of the creators of the interwar avant-garde. The issues of cinema, theater and circus, and especially their connection and confrontation, appear both in many stories of the Drohobych writer, and are an important subject of reflection by such authors as Tadeusz Peiper, Stanisław Ignacy Witkiewicz and Karol Irzykowski. The juxtaposition of literary, critical and essayistic reflection allows for an initial examination of the media a priori, the media episteme of the first decades of the 20th century, and to show how literature reflects on the new visibility and visualisation of the world.